Pengembangan Media Pembelajaran Huruf Hijaiyah Berbasis Scratch di TK Bustanul Afthal Nabire - Gunawan Prayitno; Ratna Sari; Arief Rahman Hakim (Lembaga Pengembangan Kinerja Dosen, 2025)
Learning Hijaiyah letters serves as a fundamental component in early Islamic education. However, many early childhood education institutions, including TK Bustanul Afthal Yapis in Nabire, Papua, still rely on conventional methods such as flashcards and rote memorization, which are often less engaging for young learners. This research aims to develop an interactive, educational, and contextually relevant digital learning media based on Scratch to introduce Hijaiyah letters to early learners. The study adopts a Research and Development (R&D) approach using the ADDIE model—comprising Analyze, Design, Develop, Implement, and Evaluate phases. The developed media integrates animated visuals, audio pronunciations, and clickable interactions tailored to the visual and kinesthetic learning styles of children aged 4–6 years. The preliminary implementation showed that the media significantly increased children's engagement, attention, and motivation to learn Hijaiyah letters in a fun and immersive manner. Teachers also expressed positive feedback regarding the media's user-friendliness and adaptability within classroom settings. The interface was designed to be intuitive and culturally relevant, incorporating local Papuan ornaments and character illustrations. Moreover, the application operates offline and requires minimal hardware, making it suitable for regions with limited technological infrastructure. Overall, this Scratch-based learning media presents an innovative and practical solution to enhance Islamic education for early childhood learners, especially in under-resourced educational contexts